The Paris Agreement on Climate Change - Verma, Pushp Lata (SCHOOL SCIENCE, 2018)
The impacts of climate change are further exacerbated due to increased frequency and intensity of extreme weather conditions, increase in sea level and acidification of the oceans. The Paris Agreement which lays down an ambitious action plan at limiting global warming to well below 2°C by the end of the century entered into force on 4 November 2016 after its ratification by 103 Parties of 197 Parties to the Convention. Holding the increase in the global average temperature to well below 2°C above pre-industrial levels and to pursue efforts to limit the temperature increase even further to 1.5°C above pre-industrial levels, recognizing that this would significantly reduce the risks and impacts of climate change. In COP-22, India raised the need to strengthen pre-2020 actions to close the emissions gap and lay down on a timeline for early ratification of the second commitment period of the Kyoto Protocol. India also stressed that climate justice, sustainable lifestyles and poverty eradication should be focused in future discussions.